2003
DOI: 10.1136/jnnp.74.9.1225
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing rehabilitation against standard therapy in multiple sclerosis patients receiving intravenous steroid treatment

Abstract: Background: There is evidence to support both the use of intravenous methylprednisolone (IVMP) in multiple sclerosis (MS) relapse and physiotherapy in the management of MS, but no studies have investigated the combination of steroids and rehabilitation together. Objectives: To evaluate the benefits of IVMP with planned, comprehensive multidisciplinary team (MDT) care compared to IVMP with standard care. Methods: In this randomised controlled trial, patients confirmed to have had a definite MS relapse severe en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 23 publications
0
79
0
5
Order By: Relevance
“…Multidisciplinary rehabilitation has been shown to have a positive effect on measures of functional independence including locomotion, sphincter control, and self-care. 16 In studies of health-related quality of life, improvement has been shown in fatigue, 17,18 pain, 17 general health, 17 physical health, 17,20,21 social function, 17,21 social support, 17 cognitive ability, 17 and emotional well-being. 20,21 with a neurologist, patients may contact one of four dedicated MS nurses at the outpatient clinic.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Multidisciplinary rehabilitation has been shown to have a positive effect on measures of functional independence including locomotion, sphincter control, and self-care. 16 In studies of health-related quality of life, improvement has been shown in fatigue, 17,18 pain, 17 general health, 17 physical health, 17,20,21 social function, 17,21 social support, 17 cognitive ability, 17 and emotional well-being. 20,21 with a neurologist, patients may contact one of four dedicated MS nurses at the outpatient clinic.…”
mentioning
confidence: 99%
“…2,3 Motor and cognitive impairment, fatigue, depression, pain, incontinence, sexual dysfunction, and the unpredictability of the disease reduce health-related quality of life [4][5][6][7][8][9][10][11] and participation in work and life. 2,12,13 Although it has been difficult to show the effect of multidisciplinary rehabilitation stays in clinical trials, 14,15 several studies have suggested a positive effect of multidisciplinary rehabilitation on disability [15][16][17][18][19][20][21] and aspects of health-related quality of life. 15,17,18,20,21 A review by Khan et al 15 concluded that there was strong evidence that inpatient or outpatient rehabilitation can increase activity and participation in society, despite a lack of reduction in actual impairment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because MS has a profound impact on many aspects of a person's life, the program's content and measures used to examine treatment effectiveness included several constructs, including physical functioning and emotional well-being. The favorable results observed in our study are consistent with the results reported for other conservative intervention programs that used similar treatment content designs for adults with MS. 17,31,32 For example, interventions focusing on either physical exercise 32 or educational programs 17,31 have demonstrated an equally positive impact on fatigue, depression, and/or quality of life issues for people with MS.…”
Section: Discussionmentioning
confidence: 99%
“…다발성 경화증의 증상은 주 로 감각장애, 통증, 운동마비, 시각장애가 있다. 다발성경화 증의 치료제로는 스테로이드와 면역억제제가 주로 사용되고 있으며, 이는 신체의 면역 기능을 약화시킴으로써 다발성경 화증을 조절하는 방법이다 [3][4][5]. 현재 많이 사용되는 다발성 경화증의 치료제로는 인터페론 베타 (interferon β)가 있다 [6,7].…”
Section: Introductionunclassified